Exoskeleton Design Using Kinematics Analysis for Upper Limb Rehabilitation in Post-Stroke Patients - Wahyu Eko; Sumartini Susy; Widyo Pringgo; Herdiman Lobes (E3S Web of Conferences, 2023)
Robotic technology in the last decade has developed to support the rehabilitation of post-stroke patients. The exoskeleton design model approach is carried out to simulate kinematics according to the needs of upper limb rehabilitation. The simulated design is identical to the structure of the human arm, so it requires planning and method according to the needs of human arm anatomy movements. The exoskeleton model must meet comfort and adjustment for medical rehabilitation, so it is essential to consider the kinematic analysis in its design. In this paper, we will analyze the kinematics of the exoskeleton and simulate flexion/extension and supination/pronation movements, with the targeted area being the forearm with the 3 Degrees of Freedom (DoF) mechanism consisting of two DoF. Kinematic simulations are carried out with the RoboAnalyzer software using predefined Denavit-Hartenberg parameters. The simulation results show that the end effector's initial position on the X axis is to coordinate 0 on the base 45o joint shoulder, then the rotational movement on the elbow is 1150 . In the wrist position, the action is supination and pronation because the joint is parallel to the elbow. Hence, the coordinates of the x and y-axis rotation changes follow elbow coordinates.